Aplikasi Portal Berita Berbasis Website (Studi Kasus: Lintasberita1.Com) - Priskila, Ressa; Sari, Nova Noor Kamala; Arief, Muhammad Risman (Universitas Palangka Raya, 2022)
Since its establishment on September 25, 2018, lintasberita1.com has been active in reporting for the Palangka Raya city area of Central Kalimantan Province. Currently, lintasberita1.com still uses WordPress as a blog engine for news content. The use of WordPress has limitations in that the customization that can be done is limited to what is provided by the application developer itself. Another problem occurs in the news reporting process for field journalists who still use the WhatsApp application. This process is time-consuming for editors to take news and edit it on the WordPress administrator's site for publishing. Ad management constraints also often occur because they have to manually input data. Based on these problems, the purpose of this study is to design and build a website-based news portal lintasberita1 that can accommodate user needs. The waterfall software development method was used in this study. This method has several stages, namely requirement definition, system and software design, implementation and unit testing, integration and system testing, and operation and maintenance.. This research produces a website application that can provide information on the latest news in Central Kalimantan Province, and improve the news processing process to be systematic and integrated.